An Analysis Nomoto Gain and Norbin Parameter on Ship Turning Maneuver - Aulia Siti Aisjah (IPTEK: The Journal for Technology and Science, 2010)
First order approach of maneuvering ship model developed by Nomoto, that has commonly underpinned researchers on mathematical models of ship maneuvering, is employed by the present research in order to describe the results of Nomoto validation gain value from some type of ships. In this present study, the controls are designated using FLC, while the rules are derived from FLC; furthermore, the reference is the LQG/LTR. On the other pole, Norbin parameters are obtained under the bases of the gain and time constant output control response. Validation of Nomoto gain value is obtained through the calculation of the value of a constant gain, settling time of the first order response, and approach value toward damping ratio and natural frequency response of the system used to control the output of the second order pattern. Validation is employed on 20 types of ships with a length between 40-350 meters; as a result, it is figured out that at the Low Speed General Cargo ship, Mariner, RO/RO, and Barge Carrier have good maneuverability compared to the other 17 types of ships.